PENGARUH SERVANT LEADERSHIP DAN TEAMWORK TERHADAP KEPUASAN KERJA - Istiqomah Dhiyaa Syam's Asfirman; Onsardi Onsardi (UM. Bengkulu, 2026)
This study aims to determine the influence of servant leadership and teamwork on employee job satisfaction at coffee shops in Bengkulu City. The research was conducted from December 2025 until completion. This type of research is quantitative research with a causal associative approach. The population of this study consists of operational employees at coffee shops in Bengkulu City. Data collection techniques used were observation, interviews, and questionnaires. While data analysis techniques used descriptive analysis, multiple linear regression analysis using SPSS, and coefficient of determination analysis. The results of this study indicate that servant leadership has a positive and significant effect on employee job satisfaction at coffee shops in Bengkulu City. This means that the higher the level of servant leadership applied by managers, the higher the employee job satisfaction will be. In addition, teamwork also has a positive and significant effect on employee job satisfaction at coffee shops in Bengkulu City. This shows that good teamwork will create a harmonious work environment that has a positive impact on employee job satisfaction. Servant leadership and teamwork simultaneously have a positive and significant effect on employee job satisfaction at coffee shops in Bengkulu City. This means that both factors play an important role in creating employee job satisfaction within the scope of the coffee shop industry. Keywords: Servant leadership, Teamwork, Job Satisfaction